Editorial : Digital social innovation: An overview and research framework - Qureshi, Israr; Pan, Shan L.; Zheng, Yingqin (Information Systems Journal, 2021)
Digital social innovation (DSI) involves the use of digital technologies in the development and implementation of innovative products, services, processes and business models that seek to improve the well-being and agency of socially disadvantaged groups or address social problems related to marginality, inequality and social exclusion (Qureshi, Pan, & Zheng, 2017; Shalini et al., 2021). Information Systems Frontiers, 22 (11), 1 - 21. https://doi.org/10.1007/s10796-020-09991-6 153 Parthiban, R., Qureshi, I., Bandyopadhyay, S., & Jaikumar, S. (2021). Social inclusion/exclusion (Diaz Andrade & Doolin, 2016; Iivari et al., 2018; Riaz & Qureshi, 2017); social inequality (Qureshi et al., 2018; Zheng & Walsham, 2008, 2021) Embedded agency of DSIrs How are DSIrs able to engage with local institutions yet bring change in these very same institutions? 151 Pandey, M., Bhati, M., Shukla, D. M., & Qureshi, I. (2021). 152 Parthiban, R., Qureshi, I., Bandyopadhyay, S., Bhatt, B., & Jaikumar, S. (2020).
Keywords: Digital; Réservé UdeM

Editorial : Digital social innovation: An overview and research framework - Qureshi, Israr; Pan, Shan L.; Zheng, Yingqin (Information Systems Journal, 2021)
Digital social innovation (DSI) involves the use of digital technologies in the development and implementation of innovative products, services, processes and business models that seek to improve the well-being and agency of socially disadvantaged groups or address social problems related to marginality, inequality and social exclusion (Qureshi, Pan, & Zheng, 2017; Shalini et al., 2021). Information Systems Frontiers, 22 (11), 1 - 21. https://doi.org/10.1007/s10796-020-09991-6 153 Parthiban, R., Qureshi, I., Bandyopadhyay, S., & Jaikumar, S. (2021). Social inclusion/exclusion (Diaz Andrade & Doolin, 2016; Iivari et al., 2018; Riaz & Qureshi, 2017); social inequality (Qureshi et al., 2018; Zheng & Walsham, 2008, 2021) Embedded agency of DSIrs How are DSIrs able to engage with local institutions yet bring change in these very same institutions? 151 Pandey, M., Bhati, M., Shukla, D. M., & Qureshi, I. (2021). 152 Parthiban, R., Qureshi, I., Bandyopadhyay, S., Bhatt, B., & Jaikumar, S. (2020).
Keywords: Digital; Réservé UdeM